Analisis Pengaruh Nilai Upah Dan Tenaga Kerja Terhadap Pengangguran Terbuka Di Sumatera Barat Tahun 2014-2023 - Reyhan Aulia; Risda Juniandriani; Siti Inayah; Muhammad Kurniawan (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research aims to analyze the influence of wages and labor values on the level of open unemployment in West Sumatra in the period 2014-2023. The method used is panel data regression analysis using secondary data from BPS and the West Sumatra Manpower Service. The research results show that wages have an insignificant positive influence and labor has an insignificant negative influence on the level of open unemployment in West Sumatra. In conclusion, the increase in wages and the number of workers in West Sumatra did not contribute to the level of open unemployment in the area during the 2014-2023 period. This research provides important information for the government and relevant stakeholders to design policies that can reduce the unemployment rate in West Sumatra.